Tomato Oxalyl-CoA Synthetase Degrades Oxalate and Affects Fruit Quality - Li, Pengfei; He, Qiyu; Jin, Jianfeng; Liu, Yu; Wen, Yuxin; Zhao, Kai; Mao, Guangqun; Fan, Wei; Yang, Jianli (Frontiers in Plant Science, 2022)
Acyl activating enzyme 3 (AAE3) encodes oxalyl-CoA synthetase involved in oxalate degradation. In this study, we investigated the role of AAE3 (SlAAE3) in the fruit quality of tomato (Solanum lycopersicum). The purified recombinant SlAAE3 protein from Escherichia coli exhibited a high activity toward oxalate, with a Km of 223.8 ± 20.03 μm and Vmax of 7.908 ± 0.606 μmol mg–1 protein min–1. Transient expression of SlAAE3-green fluorescent protein (GFP) fusion proteins suggests that SlAAE3 is a soluble protein without specific subcellular localization. The expression of SlAAE3 is both tissue- and development-dependent, and increased during fruit ripping. The Slaae3 knockout mutants had improved fruit quality as evidenced by the increased sugar-acid ratio and mineral nutrient content. To find the mechanism by which SlAAE3 affects fruit quality, transcriptome, and metabolome were employed on SlAAE3 over-expressed line and wide type fruits. The transcriptomic and metabolic profiles indicated that SlAAE3 in fruits mainly functions at 20 days post-anthesis (20 DPA) and mature green (MG) stages, resulting in up-regulation of amino acid derivatives, nucleotides, and derivatives, but down-regulation of lipid compounds. However, differentially expressed genes (DEGs) were mainly enriched at redox pathways. Taken together, both in vivo and in vitro results suggest that SlAAE3-encoded protein acts as an oxalyl-CoA synthetase, which also participates in redox metabolism. These data provide a further understanding of the mechanism by which SlAAE3 participates in tomato fruit quality.